High-Frequency Oscillatory Ventilation Combined with Volume Guarantee in a Neonatal Animal Model of Respiratory Distress Syndrome - Manuel Sánchez Luna; Martín Santos González; Francisco Tendillo Cortijo (Critical Care Research and Practice)
Objective. To assess volume guarantee (VG) ventilation combined with high-frequency oscillatory ventilation (HFOV) strategy on PaCO2 regulation in an experimental model of neonatal distress syndrome. Methods. Six 2-day-old piglets weighing  kg were used for this interventional experimental study. Animals were ventilated during physiologic lung conditions and after depletion of lung surfactant by bronchoalveolar lavage (BAL). The effect of HFOV combined with VG on PaCO2 was evaluated at different high-frequency expired tidal volume (VThf) at constant frequency () and mean airway pressure (mPaw). Fluctuations of the pressure (ΔPhf) around the mPaw and PaCO2 were analyzed before and after lung surfactant depletion. Results. PaCO2 levels were inversely proportional to VThf. In the physiological lung condition, an increase in VThf caused a significant decrease in PaCO2 and an increase in ΔPhf. After BAL, PaCO2 did not change as compared with pre-BAL situation as the VThf remained constant by the ventilator. Conclusions. In this animal model, using HFOV combined with VG, changes in the VThf settings induced significant modifications in PaCO2. After changing the lung condition by depletion of surfactant, PaCO2 remained unchanged, as the VThf setting was maintained constant by modifications in the ΔPhf done by the ventilator.